2022
DOI: 10.3390/diagnostics12102413
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Invasiveness and Recurrence of Pituitary Adenomas: A Series of 94 Patients

Abstract: (1) Background: The aim of the current study is to evaluate the immunohistochemical expression of Ki-67, CD-56, Cyclin-D1 and E-Cadherin in the tissues samples of pituitary adenomas (PAs) and its association with PAs clinical manifestation tumor size, invasiveness and the risk of recurrence. (2) Materials and Methods: Ninety-four patients who underwent endoscope transsphenoidal excision of PAs were included in our study. The immunohistochemical expression of the Cyclin-D1, CD-56, E-Cadherin and Ki-67 markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Hasanov et al showed that pituitary tumors with Ki-67 ≥ 3% presented more frequently as macroadenomas with cavernous sinus invasion, with higher surgery numbers and recurrence rates when compared to tumors with Ki-67 < 3% [27]. Stefanidis et al confirmed positive correlation between the Ki-67 index and tumor size, extrasellar extension, cavernous sinus invasion, as well as recurrence rate [28]. Meanwhile, Sadeghipour et al reported that the Ki-67 index was correlated with tumor invasiveness, but not with recurrence rate [29].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hasanov et al showed that pituitary tumors with Ki-67 ≥ 3% presented more frequently as macroadenomas with cavernous sinus invasion, with higher surgery numbers and recurrence rates when compared to tumors with Ki-67 < 3% [27]. Stefanidis et al confirmed positive correlation between the Ki-67 index and tumor size, extrasellar extension, cavernous sinus invasion, as well as recurrence rate [28]. Meanwhile, Sadeghipour et al reported that the Ki-67 index was correlated with tumor invasiveness, but not with recurrence rate [29].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the proliferation index Ki-67, its meaning has already been widely analyzed in pituitary tumors. It has been shown that higher Ki-67 index values were correlated with the local invasiveness and clinical aggressiveness of the tumor [27][28][29]. Hasanov et al showed that pituitary tumors with Ki-67 ≥ 3% presented more frequently as macroadenomas with cavernous sinus invasion, with higher surgery numbers and recurrence rates when compared to tumors with Ki-67 < 3% [27].…”
Section: Discussionmentioning
confidence: 99%